(Re)Envisioning Mindfulness for Leadership Retention. (March 2022) - Kim, Dong Jin; Pendola, Andrew
An emerging body of research has shown that mindfulness practices for school administrators can result in significant benefits, including a reduction in stress and sense of burnout. Concurrently, nearly 20% of school principals exit their position each year—and cite high levels of stress as a primary motivating factor. In this conceptual paper, we seek to align the benefits of mindfulness practices for educators to the causes of principal turnover, as a means to better support local, low-cost strategies to reduce high levels of leadership attrition. We offer a framework that aligns mindfulness research with principal retention research, and follow with an identification of the organizational, social, and cultural barriers to the adoption of mindfulness practices in public schools. We conclude with specific recommendations for school and district leadership to incorporate mindfulness-based interventions into organizational practices in order to help reduce administrator stress, improve task focus, and ultimately address the underlying sources of leadership turnover.